Regulatory Framework and Clinical Translation of Automated Cell Production in China - Jianwen Deng (Journal of Health Sciences and Clinical Technology, 2026)
The clinical translation of cell therapies in the People's Republic of China has experienced unprecedented growth, transitioning from early experimental stages to the industrialization of automated cell production. This review comprehensively analyzes the evolving regulatory framework governing cell and gene therapies in China, with a specific focus on the dual-track regulatory system managed by the National Medical Products Administration (NMPA) and the National Health Commission (NHC). We evaluate key legal clauses, including the Good Manufacturing Practice (GMP) guidelines for cell therapy products and the Biosafety Law, which collectively mandate the shift toward closed, automated manufacturing systems. Furthermore, this article reviews recent clinical findings from 20 to 30 scholarly studies, highlighting the clinical outcomes of NMPA-approved chimeric antigen receptor T-cell (CAR-T) therapies and the automated expansion of mesenchymal stem cells (MSCs). The synthesis of regulatory policy and clinical evidence demonstrates that automated production is not only a compliance requirement but a critical determinant of therapeutic efficacy and patient safety in China's rapidly advancing regenerative medicine sector.